Influence of the rotary and/or oscillatory reciprocating systems in the morphological changes of narrow and curved molar root canals anatomy - Rosa, Joedy Maria Costa Santa; Dametto, Fábio Roberto; Gadê-neto, Cicero Romão; Carvalho, Rejane Andrade De; Albuquerque, Diana Santana De; Pameijer, Cornelis; Tanomaru-filho, Mário [UNESP]; Leonardo, Renato de Toledo [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
OBJECTIVE: This study evaluated four mechanized Endodontic systems, ProTaper Universal, K3 Endo, Twisted file (rotary) and the oscillatory reciprocating system Endo - Eze TiLOS, in order to verify and measure alterations in original anatomy with deviations at cervical, medium and apical root canal thirds. MATERIAL AND METHOD: It was used MB root canals of 60 extract human lower molars, to produce a line of severe angles, according to the classification of Schneider. Samples were included in Ester vinyl resin, mounted in the Teflon Furnace, transversally sectioned at the cervical, middle and apical thirds, which were subsequently photographed using a digital camera Cyber Shot DSC-TX10,attached to an operating microscope 3101XY DFVasconcelos with 40× magnification in order to measure the anatomical transversal area of the root canal, using the software AutoCAD 2008, comparing pre and post-instrumentation. All samples assembled in the Furnace also were submitted to x-ray in a standardized way to enable the comparison of the angle of Schneider pre-and post-instrumentation. Once collected the data, they were compared statistically using the program BioEstat 5.0. RESULT: The analysis of the results showed that in the cervical third, rotary systems were more effective than Endo-Eze TiLOS System with statistically significant differences (p ≤ 0,05). Apical and middle third changes in anatomy were similar, but apically, the ProTaper system caused more deviations when comparing the angle of Schneider,and areas before and after instrumentation(p ≤ 0,05). CONCLUSION: It was concluded that all the systems caused alteration in the original anatomy of the root canal when parameters as angle of Schneider and areas before and after preparation were used.

OBJETIVO: Esse estudo avaliou quatro sistemas endodônticos mecanizados, ProTaper Universal, K3 Endo, Twisted file, (rotatórios) e Endo - Eze TiLOS(oscilatório) para verificar e medir as alterações na anatomia original do canal radicular e desvios nos terços cervical,médio e apical. MATERIAL E MÉTODO: Foram utilizadas 60 raízes mésio‑vestibulares de molares inferiores extraídos de humanos para coleta de medições de ângulos e classificação de Schneider. Os espécimes foram incluídos em resina de Éster vinil e montadas em muflas de Teflon, seccionadas transversalmente nos terços cervical,médio e apical para posterior fotografia usando-se câmera digital Cyber Shot DSC-TX10,acoplada à um microscópio 3101XY DFVasconcelos com 40× de aumento para se mensurar a àrea da secção anatômica transversal do canal radicular utilizando o programa AutoCAD 2008, comparando as àreas pré e pós instrumentação. Todos os espécimes ajustados na mufla foram radiografados de maneira padronizada para permitir a avaliação do ângulo de Schneider pré e pós-instrumentação.Uma vez coletados os dados,os mesmos foram comparados estatisticamente usando-se o programa BioEstat 5.0. RESULTADO: A análise dos resultados mostrou que no terço cervical os sistemas rotatórios foram mais eficazes que o sistema oscilatório Endo-Eze TiLOS,com diferenças estatisticamente significantes (p ≤ 0,05). As alterações anatômicas relativas ao desvio nos terços apical e médio foram similares, mas apicalmente o sistema ProTaper promoveu mais desvios quando se avaliou o ângulo de Schneider pré e pós instrumentação (p ≤ 0,05). CONCLUSÃO: Utilizando-se a alteração do ângulo de Schneider e a diferença entre área dentinária inicial (antes do preparo) e final (pós-preparo), concluiu-se que todos os sistemas causaram desvio na anatomia original do canal radicular.
Influência dos sistemas rotatórios e/ou oscilatórios recíprocos nas alterações morfológicas anatômicas de canais radiculares atresiados e curvos
Keywords: Root canal therapy; instrumentation; endodontics; Tratamento de canal radicular; instrumentação; endodontia